ORIENTASI PEMBEBASAN HAK-HAK PEREMPUAN DALAM AYAT-AYAT ‘IDDAH DI MA’HAD AL-QUR’AN UNIVERSITAS PTIQ JAKARTA - Muhammad Hariyadi; Nur Rahami; Nur Afif; Risma Hikmawati; Ahmad Zain Sarnoto; Siti Musdah Mulia (MPP: Lembaga Penelitian Dan Studi Kebijakan, 2025)
The gender equality argument that desires reciprocity between men and women in all aspects, including 'iddah, which seems to burden only women with its implementation, suggests the need for a re-reading or reinterpretation of the verses related to this matter. This research uses qualitative research methods by examining Asma Barlas' thoughts related to 'iddah. The concept of 'Iddah is the Quran's response to the patriarchal pre-Islamic Arab social conditions; this concept is an initial step towards liberating women's rights. Regarding the burden of 'iddah, which is only obligatory for women, if examined from its historical perspective, it may be possible for men to also be subject to 'iddah, but certainly with different terminology or perhaps with a redefinition of the term 'iddah. Asma Barlas, who is very passionate about instructing the re-reading of Quranic texts, experiences shortcomings in reinterpreting these texts due to her still abstract method